2022
DOI: 10.3389/fnut.2022.832757
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Ramadan Like Fasting Effects on the Gut Microbiome in BALB/c Mice

Abstract: Recently we reported that in healthy volunteer Ramadan-associated intermittent fasting (RAIF) remodels the gut microbiome and resulted in an increase in small chain fatty acid producing bacteria concomitant with improved metabolic parameters. As interpretation of these results is hampered by the possible psychological effects associated with the study, we now aim to investigate RAIF in experimental animals. To this end, 6-week male BALB/c mice were subjected to RAIF (30 days of a 16-h daily fasting; n = 8) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
6
1
Order By: Relevance
“…Interestingly, these results are consistent with changes in SCFAs, including acetic acid, butyric acid, and propionic acid. Although the limited sample size for the SCFA assessment did not allow for the calculation of statistical p-values among the groups, the apparent decrease in the three SCFAs during the Ramadan fasting period and their return to normal levels after refeeding confirm our findings and also contradict previous studies [11][12][13][14][15][16]. Furthermore, the association between the three assessed SCFAs and microorganisms has helped us understand the health-related roles of microbial communities.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…Interestingly, these results are consistent with changes in SCFAs, including acetic acid, butyric acid, and propionic acid. Although the limited sample size for the SCFA assessment did not allow for the calculation of statistical p-values among the groups, the apparent decrease in the three SCFAs during the Ramadan fasting period and their return to normal levels after refeeding confirm our findings and also contradict previous studies [11][12][13][14][15][16]. Furthermore, the association between the three assessed SCFAs and microorganisms has helped us understand the health-related roles of microbial communities.…”
Section: Discussioncontrasting
confidence: 58%
“…In recent decades, Ramadan fasting has been equated with intermittent fasting, and thus, has been promoted for its potential health benefits [ 43 , 44 , 45 ]. Preliminary studies investigating the potential relationship between Ramadan fasting and the gut microbiome have employed either a cross-sectional design comparing a fasting group (those participating in Ramadan fasting) with a group refeeding after Ramadan [ 11 , 12 , 13 ], or have used a longitudinal design monitoring changes in the gut microbiota over the course of the Ramadan month [ 14 , 15 , 16 ]. To the best of our knowledge, this is the first study to track changes in the gut microbiome throughout and then after Ramadan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Maifeld et al ( 2021 ) found that members of Clostridia showed an opposite effect with the fasting treatment in the gut microbiome of humans. An enrichment in the family Rikenellaceae was already found in the gut microbiome of rodents after a fasting treatment: Zhang et al ( 2020 ) determined an increase of Rikenellaceae in the intermittent energy fasting group in the gut microbiome of a colitis mouse model and Su et al ( 2022 ) found similar results in the gut microbiome of BALB/c mice after Ramadan fasting. We could argue that the increase in the abundance of the members of Helicobacter in the fasting groups could be related to a reduction in the microbiome-mediated colonization resistance against potential pathogens of the gut microbiota of the guinea pig (Ducarmon et al, 2023 ).…”
Section: Discussionmentioning
confidence: 88%
“…Butyric acid, one of the major members of the short-chain fatty acids, is produced in the intestine mainly by the enzymatic digestion of dietary fiber and is used as the main energy source for the intestinal epithelium ( Ye et al., 2021 ). Butyrate-producing bacteria include Ruminococcaceae ( Su et al., 2022 ), Butyrivibrio , etc., which increase the content of butyrate in the intestine, enhancing the activity of bile salt hydrolase (BSH) and increasing free bile acids in the intestinal lumen, while hydrophobic free bile acids are not easily reabsorbed by the intestine and are excreted in the feces ( Wang et al., 2012 ; Ye et al., 2021 ). To compensate for the loss of bile acids, the liver uses the cholesterol in the blood as a raw material to synthesize bile acids, thus speeding up the process of converting cholesterol into bile acids, resulting in lower cholesterol in the blood and reducing the formation of gallbladder stone ( Wang et al., 2012 ; Ye et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%